A new Microlicia (Melastomataceae: Microlicieae) from the Southern Cadeia do Espinhaço, Minas Gerais, Brazil - Almeda, Frank; Fidanza, Karina (Phytotaxa, 2020)
Microlicia pacificoi is described as a new species from a limited area of the southern Cadeia do Espinhaço in Minas Gerais, Brazil. Line drawings, photographs, a distribution map, and comparative notes on morphologically similar species are provided. This species is readily distinguished by its wiry habit, narrowly lanceolate sessile leaf blades that are 2.5–4 × 0.5–1 mm and resinous-punctate on both surfaces, delicate gland-tipped trichomes on distal internodes and hypanthia, and glabrous irregularly rugulate calyx lobes that are caducous following anthesis.